2022
DOI: 10.1108/jocm-04-2021-0127
|View full text |Cite
|
Sign up to set email alerts
|

I cannot be creative due to my exploitative leader! A moderated mediation interplay of leader–member exchange quality and knowledge hiding

Abstract: PurposeWith an emphasis on displaced aggression theory and social exchange theory, this study aims to investigate the harmful effects of exploitative leadership (EL) on employee creativity (EC) through the mediating role of knowledge hiding (KH). Moreover, this study examines the boundary effects of leader–member exchange (LMX) to explore conditions under which KH is more or less likely to occur.Design/methodology/approachThe study employed time-lagged (i.e. three-wave), multisource (i.e. self-rated and peer-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 82 publications
(218 reference statements)
0
11
0
Order By: Relevance
“…As this study showed, the frustration-aggression-displacement theory offers a useful lens of analysis to explore the impact of interactional justice on counterproductive knowledge behavior. In a similar vein, Feng et al (2022) and Pradhan et al (2020) confirm that exploitative and abusive leaders make individual employees displace their aggression onto neutral targets (i.e. their co-workers) and hide knowledge from them.…”
Section: Implications For Theorymentioning
confidence: 76%
“…As this study showed, the frustration-aggression-displacement theory offers a useful lens of analysis to explore the impact of interactional justice on counterproductive knowledge behavior. In a similar vein, Feng et al (2022) and Pradhan et al (2020) confirm that exploitative and abusive leaders make individual employees displace their aggression onto neutral targets (i.e. their co-workers) and hide knowledge from them.…”
Section: Implications For Theorymentioning
confidence: 76%
“…Additionally, the study calculated the “goodness-of-fit index” (GFI) – “the geometric mean of the average communality and average R 2 ”, using the diagnostic tool. 65 , 66 With a value of 0.547 higher than the threshold value of 0.36 for a significant effect size of R 2 , the GFI results are displayed in Table 5 , indicating a good model fit. 79 In addition, Stone-Geisser’s Q 2 was evaluated with an “omission distance” of 5.…”
Section: Resultsmentioning
confidence: 95%
“…As shown in Table 1, only one study was found to investigate the impact of exploitative leadership on knowledge sharing by considering the moderating role of organizational citizenship (Abdulmuhsin et al ., 2021), but how exploitative leadership impacts knowledge sharing is unknown. Though some studies have explored the relationship between exploitative leadership and knowledge hiding (Guo et al ., 2020; Syed et al ., 2021; Feng et al ., 2022), only one of them investigated the mediating role of psychological distress in such a relationship (Guo et al ., 2020). Other possible psychological mechanisms (e.g.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…organization-based self-esteem) have not been examined. To weaken the positive impact of exploitative leadership on knowledge hiding, these three studies have examined different boundary conditions, such as hostile attribution bias (Guo et al ., 2020), fear of negative evaluation (Syed et al ., 2021) and leader-member exchange (Feng et al ., 2022). However, the role of other important organizational factors (e.g.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%